Etching of Art Deco buildings along Maharshi Karve Marg - Ayan Ghosh (2023)
Elevation drawings of Art Deco buildings along Maharshi Karve Road. Seen here are Queen's Court, Green Fields, Swastik Court, and Motabhoy Mansion. These were all built in the 1930s decade, during a flurry of building activity on land reclaimed from the Arabian Sea as part of the Back Bay Land Reclamation Scheme, which started in 1928.